2018
DOI: 10.1039/c8fo00643a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of EPA-enriched ethanolamine plasmalogen and EPA-enriched phosphatidylethanolamine on Aβ42 induced cognitive deficiency in a rat model of Alzheimer's disease

Abstract: Ethanolamine plasmalogen (pPE), a major phospholipid in neuronal membranes, is specifically reduced in postmortem brains from patients with Alzheimer's disease (AD). The purpose of the present study was to compare the effects of EPA-enriched ethanolamine plasmalogen (EPA-pPE) and EPA-enriched phosphatidylethanolamine (EPA-PE) on cognitive deficiency and illustrate the possible underlying mechanisms. SD rats were divided into four groups including the sham group injected with 0.9% saline and three amyloid-β (Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 30 publications
6
32
0
1
Order By: Relevance
“…Previous studies have suggested that Alzheimer's disease is directly or indirectly related to neuronal apoptosis . Our previous studies demonstrated that intracerebroventricular injection of A β 1–42 caused neuronal apoptosis . What is more, previous study showed that cerebrosides isolated from the seeds of S. lychnophora could protect SH‐SY5Y cell against damage induced by hydrogen peroxide .…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have suggested that Alzheimer's disease is directly or indirectly related to neuronal apoptosis . Our previous studies demonstrated that intracerebroventricular injection of A β 1–42 caused neuronal apoptosis . What is more, previous study showed that cerebrosides isolated from the seeds of S. lychnophora could protect SH‐SY5Y cell against damage induced by hydrogen peroxide .…”
Section: Resultsmentioning
confidence: 94%
“…Natural sources of plasmalogen are not readily available, and thus dietary approaches to increase plasmalogen deficiency in RCDP are not feasible. Plasmalogen extracts have been generated from animal and marine tissues and tested in rodent models of Alzheimer's disease (Che et al, 2018;Hossain et al, 2018;Sejimo et al, 2018;Yamashita et al, 2017) and human patients with mild Alzheimer's disease (Fujino et al, 2017). The animal studies showed an improvement in the cognitive impairment and reduction in the neuroinflammation associated with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the extrinsic supply of PlsEtn bearing n‐3 PUFA suppresses neuronal apoptosis through the mitochondrial pathway and improves impaired memory in a rat model of AD (Yamashita et al, 2015, 2016a, 2017a). In addition, EPA‐enriched PlsEtn rather than EPA‐enriched PtdEtn alleviated amyloid β‐induced neurotoxicity by inhibiting oxidative stress, neural injury, apoptosis, and neuro‐inflammation, which depended on the vinyl ether linkage in the sn ‐1 position (Che et al, 2018). However, the functional role of dietary PlsEtn in the health of intestines remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the demonstrated superiority of PlsEtn over PtdEtn in neuroprotective functions (Che et al, 2018) and the relationship of PlsEtn levels and a dysfunction in the colon mucosa (Lopez et al, 2018) as aforementioned, we hypothesized that dietary intake of PlsEtn may suppress colon inflammatory stress and subsequent formation of colon precancerous lesions (aberrant crypt foci – ACF) possibly due to a high presence of alkenyl (vinyl ether) linkages. In the present study, we elucidated the effect of diets supplemented with purified EtnGpl consisting of high and low PlsEtn ratios on the formation of ACF using a 1,2‐dimethylhydrazine (DMH)‐induced colon carcinogenesis mice model.…”
Section: Introductionmentioning
confidence: 99%